The physics of solar energy conversion - Bisquert, Juan (CRC Press, 2020)
"The conceptual picture of a solar cell has evolved in the last two decades, a broad landscape of candidate materials and devices were discovered and systematically studied and reported. New concepts and a rather powerful picture embracing very different types of devices has emerged from many discussions and sometimes also conceptual clashes. This handbook introduces the main physico-chemical principles that govern the operation of energy devices. The work presents an explanation of the operation of photovoltaic devices with a broad perspective that embraces concepts from nanostructured and highly disordered materials to highly efficient devices such as lead halide perovskite solar cells"--